Penanaman Nilai-Nilai Karakter dengan Pendekatan Student Centered Learning pada MKWU-PAI di Perguruan Tinggi Umum - Iwan Hermawan; Nok Nasibah; Uus Ruswandi; Bambang Samsul Arifin (Universitas Muhammadiyah Enrekang, 2021)
Education is not just about the learning process for knowledge, understanding, and skills, but the substance of education is to shape human character with good values ​​that come from norms, ethics, customs, and religions. By referring to the five pillars of character found in strengthening character education in Indonesia, the inculcation of character values ​​in the education process requires an appropriate, appropriate, and effective learning model approach. One of the learning model approaches to instill character values ​​is the student-centered learning model approach or learning model that provides flexibility for students to be active, creative, innovative, inspirational, interactive, independent, collaborative, cooperative, and contextual. There is harmony between the student-centered learning approach and character education because both instill and foster good character values. The methods used to support the learning process referred to are discussion, problem-based, and project-based methods. Based on that, this research is a development (research and development) that starts from the process of developing, collaborating, and perfecting the learning model between the values ​​of strengthening character education and the student-centered learning approach at MKWU-PAI in Public Universities.